Perceived control and quality of life among recipients of implantable cardioverter defibrillator. Issue 5 (September 2019) - Hammash, Muna; McEvedy, Samantha M.; Wright, Jesse; Cameron, Jan; Miller, Jennifer; Ski, Chantal F.; Thompson, David R.; Biddle, Martha J.; Wimsatt, Amy; Schrader, Melanie; Smith, Rachel Vickers; Chung, Misook L.; et al.
Abstract: Background: Perceived control is strongly associated with health-related quality of life (HRQOL) among patients with chronic conditions, and it is possible to increase perceived control with appropriate intervention. Little is known about the relationship between perceived control and HRQOL in implantable cardioverter defibrillator (ICD) recipients. Objectives: To determine the relationship of perceived control with quality of life in ICD recipients and to determine predictors of perceived control in this population. Methods: A total of 263 ICD recipients (63% male, age 61 ± 14 years) completed the Control Attitude Scale-Revised to measure perceived control and completed self-reported measures on potential correlates of perceived control (i.e., depressive symptoms, anxiety, social support, and ICD concerns). The EuroQol-5D was used to measure HRQOL. Regression analysis was used to determine predictors of perceived control and its relationship to HRQOL, controlling for covariates. Results: Lower perceived control (β = 0.30, p < .01), and higher levels of depression (β = −0.30, p < .01) and anxiety (β = −0.18, p < .05) predicted lower levels of HRQOL. Higher anxiety (β = −0.17, p < .05), higher depression (β = −0.23, p < .05), lower social support (β = 0.26, p < .01), and higher ICD-related concerns (β = −0.16, p < .05) independently predicted lower perceived control. Conclusions: Interventions targeting patients' ICD concerns and psychosocial factors before, and continuing after, ICD insertion are needed to improve ICD recipients' perceived control and, in turn, their HRQOL.